Activation of brainstem and midbrain nuclei during cognitive control in medicated patients with schizophrenia. Issue 1 (5th September 2018) - Köhler, Stefanie; Wagner, Gerd; Bär, Karl‐Jürgen
Abstract: Evidence suggests that cognitive control functions as well as the underlying brain network, anchored by the prefrontal cortex (PFC) and the dorsal anterior cingulate cortex (dACC), are dysfunctional in schizophrenia. Catecholamine producing midbrain and brainstem nuclei are densely connected with the PFC and dACC and exert profound contributions to cognitive control processes. Dysfunctions within the underlying neurotransmitter systems are considered to play a central role in the occurrence of various symptoms of schizophrenia. We sought to investigate the putatively abnormal activation pattern of the dopaminergic midbrain nuclei, that is, ventral tegmental area (VTA) and substantia nigra as well as that of the noradrenergic locus coeruleus (LC) in patients with schizophrenia during cognitive control. A total of 28 medicated patients and 27 healthy controls were investigated with the manual version of the Stroop task using event‐related fMRI. The main finding was a reduced BOLD activation in the VTA during both Stroop task conditions in patients in comparison to controls, which correlated significantly with the degree of negative symptoms. We further detected a comparable LC activation in in patients and healthy controls. However, in controls LC activation was significantly correlated with the Stroop interference time, which was not observed in patients. The finding of reduced VTA activation in schizophrenia patients lends further support to the assumed dysfunction of the DA system in schizophrenia. In addition, despite comparable LC activation, the nonsignificant correlation with the Stroop interference time might indicate altered LC functioning in schizophrenia and, thus, needs further investigations.